Além do aprendizado da cultura brasileira: recorte sobre a tolerância à ambiguidade cultural em estudos de caso de PL2 e PLE - Regina Ramos-Sollai , Sílvia (Revista Vozes dos Vales: Publicações Acadêmicas, 2025)
This qualitative article aims at exploring text samples produced by foreign students and native teacher of Portuguese and Lusophone culture, in which the students present themselves as target culture specialists. The data collection, the oral presentation transcriptions, and the elements mapping that recur from Portuguese as a second language and Portuguese as a foreign language classes showed the student get hold of a certification tool so as to define the other culture, even if temporarily. In a metalinguistic function, the ongoing communicative independence per se enables the students to use the target language in order to define the target culture. Concomitantly, their teacher alternates between moments of persuasion and strangeness about his or her own culture. Moreover, results point to a hybridization trend, and a cultural authenticity as well.
Keywords: Metalinguistic fuction; Target language; Target culture; Hybridization; Cultural authenticity